Direct measurement of wall slip and slip layer thickness of non-Brownian hard-sphere suspensions in rectangular channel flows - Jesinghausen, Steffen; Weiffen, Rene; Schmid, Hans-Joachim (Experiments in Fluids)
Wall slip is a long-known phenomenon in the field of rheology. Nevertheless, the origin and the evolution are not completely clear yet. Regarding suspensions, the effect becomes even more complicated, because different mechanisms like pure slip or slip due to particle migration have to be taken into account. Furthermore, suspensions themselves show many flow anomalies and the isolation of slip is complicated. In order to develop working physical models, further insight is necessary. In this work, we measured experimentally the wall slip velocities of different highly filled suspensions in a rectangular slit die directly with respect to the particle concentration and the particle size. The slip velocities were obtained using a particle image velocimetry (PIV) system. The suspensions consisting of a castor oil–cinnamon oil blend and PMMA particles were matched in terms of refractive indexes to appear transparent. Hereby, possible optical path lengths larger than 15 mm were achieved. The slip velocities were found to be in a quadratic relation to the wall shear stress. Furthermore, the overall flow rate as well as the particle concentration has a direct influence on the slip. Concerning the shear stress, there seem to be two regions of slip with different physical characteristics. Furthermore, we estimated the slip layer thickness directly from the velocity profiles and propose a new interpretation. The PIV technique is used to investigate the viscosity and implicit the concentration profile in the slit die. It is shown that the particle migration process is quite fast.
Keywords: Rheology; Wall Slip; Slip; apparent slip; suspension

Hans Werner Henze - Tumat, Antje (Lexikon der Oper)

Projekt WiGeMath: Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Schürmann, Mirko; Biehler, Rolf; Hochmuth, Reinhard Karl; Schaper, Niclas; Liebendörfer, Michael (Working Paper Studieneingangsphase Perspektiven aus der Begleitforschung zum Qualitätspakt Lehre)

Wirkung und Gelingensbedingungen von Unterstützungsmaßnahmen für mathematikbezogenes Lernen in der Studieneingangsphase - Colberg, Christoph; Biehler, Rolf; Hochmuth, Reinhard; Schaper, Niclas; Liebendörfer, Michael; Schürmann, Mirko (Beiträge zum Mathematikunterricht 2016)

Fallbeispiele im Herforder Rechtsbuch im Kontext der Urteilsaufzeichnungen des späten Mittelalters - Wallmeier, Nadine (Textsortenwandel vom 9. bis 19. Jahrhundert. Akten zur internationalen Fachtagung an der Universität Paderborn vom 9.-13.06.2015.)

Jugend als soziales Kampffeld? Die Konstruktion von Jugend und Jugendpolitiken in Europa zwischen wohlfahrtstaatlicher Regulierung und Politiken der Partizipation - Dahmen, Stephan (Jugendpolitiken. Wie geht Gesellschaft mit "ihrer" Jugend um?)

Are international accounting standards more credit relevant than domestic standards? - Florou, Annita; Kosi, Urska; Pope, Peter F (Accounting and Business Research)
We examine whether the credit relevance of financial statements, defined as the ability of accounting numbers to explain credit ratings, is higher after firms are required to report under International Financial Reporting Standards (IFRS). We find an improvement in credit relevance for firms in 17 countries after mandatory IFRS reporting is introduced in 2005; this increase is higher than that reported for a matched sample of US firms. The increase in credit relevance is particularly pronounced for higher risk speculative-grade issuers, where accounting information is predicted to be more important; and for IFRS adopters with large first-time reconciliations, where the impact of IFRS is expected to be greater. These tests provide reassurance that the overall enhancement in estimated credit relevance is driven by accounting changes related to IFRS adoption. Our results suggest that credit rating analysts’ views of economic fundamentals are more closely aligned with IFRS numbers, and that analysts anticipate at least some of the effects of the IFRS transition.
Keywords: IFRS; debt markets; credit ratings; credit relevance

Accounting quality in private firms during the transition to international standards - Valentincic, Aljosa; Novak, Ales; Kosi, Urska

Suggestions for Vocabulary Focused Reading Lessons for Mainstream Classrooms Addressing Both L1 and L2 Learners - Seifert, Susanne; Kulmhofer, Andrea; Paleczek, Lisa; Schwab, Susanne; Gasteiger-Klicpera, Barbara (Early Childhood Education Journal)
Keywords: Developmental and Educational Psychology; Education

Einsatz der Widerstandserwärmung bei hydraulischen Schneidgeräten zum Trennen von hochfesten Stahlwerkstoffen in Kraftfahrzeugen - Siewers, Bernd
Die zunehmend eingesetzten hochfesten Stähle im Automobilbau können zu schwerwiegenden Problemen bei Verkehrsunfällen führen, da hydraulische Schneidgeräte zur Befreiung von Personen an ihre mechanischen Grenzen geraten. Ein Ansatz zur Behebung dieses Problems kann die Widerstandserwärmung der zu schneidenden Werkstoffe sein. Im Rahmen dieser Dissertation wurde durch Werkstoffuntersuchungen ermittelt, dass die hochfesten Stähle einen starken Abfall der Festigkeit aufweisen, während bei denselben Temperaturen potentielle Schneidwerkstoffe deutlich höhere Festigkeiten besitzen. Das Konzept wurde schließlich in einem Funktionsmuster umgesetzt. Schneidversuche zeigten, dass durch die Widerstandserwärmung ein deutlicher Abfall der erforderlichen Schneidkraft erreicht werden konnte. Insgesamt konnte gezeigt werden, dass die Widerstandserwärmung ein vielversprechendes Konzept darstellt, um hochfeste Karosseriestähle zuverlässig und schnell zu durchtrennen und somit die Befreiung eingeschlossener Fahrzeuginsassen zu gewährleisten.
Keywords: Leichtbau; Hybridsysteme; Werkstoffe

Middlebrow and Gender: 1890-1945

The Thermal Oxidation of TiAlN High Power Pulsed Magnetron Sputtering Hard Coatings as Revealed by Combined Ion and Electron Spectroscopy - Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Advanced Materials Interfaces)

Electric potential screening on metal targets submitted to reactive sputtering - Corbella, Carles; Marcak, Adrian; von Keudell, Achim; de los Arcos de Pedro, Maria Teresa (Journal of Vacuum Science & Technology A: Vacuum, Surfaces, and Films)

Nitridische und oxinitridische HPPMS-Beschichtungen für den Einsatz in der Kunststoffverarbeitung (Teil 1) - Bobzin, Kirsten; Grundmeier, Guido; Brögelmann, Tobias; de los Arcos de Pedro, Maria Teresa; Wiesing, Martin; Kruppe, Nathan C. (Vakuum in Forschung und Praxis)

(Cr,Al)N/(Cr,Al)ON Oxy-nitride Coatings deposited by Hybrid dcMS/HPPMS for Plastics Processing Applications - Bobzin, K.; Brögelmann, T.; Grundmeier, G.; de los Arcos de Pedro, Maria Teresa; Wiesing, M.; Kruppe, N.C. (Surface and Coatings Technology)

Influence of O2 exposure on the interaction between CH4 and amorphous AlYB14 - Hunold, Oliver; Wiesing, Martin; de los Arcos de Pedro, Maria Teresa; Music, Denis; Grundmeier, Guido; Schneider, Jochen M. (Applied Surface Science)

Revising secondary electron yields of ion-sputtered metal oxides - Corbella, Carles; Marcak, Adrian; de los Arcos de Pedro, Maria Teresa; von Keudell, Achim (Journal of Physics D: Applied Physics)

An efficient PE-ALD process for TiO2 thin films employing a new Ti-precursor - Gebhard, M.; Mitschker, F.; Wiesing, M.; Giner, I.; Torun, B.; de los Arcos de Pedro, Maria Teresa; Awakowicz, P.; Grundmeier, G.; Devi, A. (Journal of Materials Chemistry C)
A new Ti-precursor for low-temperature PE-ALD of titanium dioxide thin films as gas barrier layers on polymer substrates.

Combined Electrochemical and Electron Spectroscopic Investigations of the Surface Oxidation of TiAlN HPPMS Hard Coatings - Wiesing, Martin; to Baben, Moritz; Schneider, Jochen M.; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Electrochimica Acta)

Single-Mode Parametric-Down-Conversion States with 50 Photons as a Source for Mesoscopic Quantum Optics - Harder, Georg; Bartley, Tim; Lita, Adriana E.; Nam, Sae Woo; Gerrits, Thomas; Silberhorn, Christine (Physical Review Letters)

A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor - Mahnken, Rolf; Caylak, Ismail; Dridger, Alex (A Stochastic Finite Element Method with a Deviatoric-volumetric Split for the Stochastic Linear Isotropic Elasticity Tensor)
This paper presents a numerical method for solution of a stochastic partial differential equation (SPDE) for a linear elastic body with stochastic coefficients (random variables and/or random fields). To this end the stochastic finite element method (SFEM) is employed, which uses W IENER’S polynomial chaos expansion in order to decompose the coefficients into deterministic and stochastic parts. As a special case, we consider isotropic material behavior with two fluctuating parameters. Computational approaches involving GALERKIN projection are applied to reduce the SPDE into a system of deterministic PDEs. Furthermore, we consider normally distributed random variables, which are assumed to be stochastically independent, and which establish the number of stochastic dimensions. Subsequently, the resulting finite element equation is solved iteratively. Finally, in a representative example for a plate with a ring hole we study the influence of different variances for material parameters on the variances for the finite element results.

Modeling of variant-interaction during bainitic phase transformation - Ehlenbröker, Ulrich; Mahnken, Rolf; Petersmann, M; Antretter, T (IOP Conference Series: Materials Science and Engineering)

Extension of a multi-mechanism model: Hardness-based flow and transformation induced plasticity for austenitization - Cheng, C.; Mahnken, Rolf (International Journal of Solids and Structures)

Macromodelling of Transformation Induced Plasticity combined with Viscoplasticity for Low-Alloy Steels - Schneidt, Andreas; Mahnken, Rolf (steel research international)

Determination of effective properties for CFRP curing coupled to viscoleasticity based on a three-scale framework - Dammann, Christian; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase field and diffusion models for lower bainite transformation - Düsing, Martin; Mahnken, Rolf (PAMM)

Two accuracy improvements on nonuniform transformation field analysis for plasticity coupled to softening - Ju, Xiaozhe; Mahnken, Rolf (PAMM)

A thermodynamic framework for coupled multiphase Ginzburg-Landau/Cahn-Hilliard systems for simulation of lower bainitic transformation - Düsing, Martin; Mahnken, Rolf (Archive of Applied Mechanics)

A three-scale framework for fibre-reinforced-polymer curing part II: Mesoscopic modeling and macroscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

A three-scale framework for fibre-reinforced-polymer curing Part I: Microscopic modeling and mesoscopic effective properties - Mahnken, Rolf; Dammann, Christian (International Journal of Solids and Structures)

An NTFA-based homogenization framework considering softening effects - Ju, X.; Mahnken, Rolf (Mechanics of Materials)

Design of voltage controlled oscillators (VCOs) in D-band and their phase noise measurements using frequency down-conversion - Ali, U.; Bober, M.; Thiede, Andreas (2016 11th European Microwave Integrated Circuits Conference (EuMIC))

Near infrared Kerr effect and description of field-induced phase transitions in polymer-stabilized blue phase liquid crystals - Atorf, B.; Rasouli, H.; Nordendorf, G.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

The International Liquid Crystal Society 1990–2015 - Dunmur, David; Kitzerow, Heinz-Siegfried (Liquid Crystals Today)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Comparison of Cost and Complexity for Various 16-QAM Transmitter Structures in Coherent Optical Systems - Al-Bermani, Ali; Noé, Reinhold (NEXT-GENERATION OPTICAL COMMUNICATION: COMPONENTS, SUB-SYSTEMS, AND SYSTEMS V)

Die Welt 'im schönsten Fall' - Umbruchs- und Katastrophenszenarien im Werk Angela Krauß - Morrien, Rita (Umwelt - sozial, kulturell, ökologisch. Zur Darstellung von Zeitgeschichte in deutschsprachiger Gegenwartsliteratur)

Spuren des Dialogs - literatur- und kulturwissenschaftliche Überlegungen zum Thema Dialog. 50 Jahre diplomatische Beziehungen zwischen Deutschland und Israel - Morrien, Rita (Traces of Dialogue. Symposion and exhibition 2015 between Israel/Rishon LeZion and Germany/Münster)

LiNbO3-Based Endless Optical Polarization Control The Photonic Alternative to Coherent Electronics - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Time-resolved Mueller matrix measurement and polarization scrambler characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

LiNbO3-based endless optical polarization control - Noé, Reinhold; Koch, Benjamin; Mirvoda, Vitali (2016 21st European Conference on Networks and Optical Communications (NOC))

Accelerated Testing of Polarization-Tracking Receiver Using Polarization Scrambler with Peaked Speed Distribution - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali; Sandel, David (Photonic Networks; 17. ITG-Symposium; Proceedings of)

Catalani, Angelica - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Tetrazzini, Luisa - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Patti, Adelina - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Pasta, Giuditta - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Lind, Jenny - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Gender - Grotjahn, Rebecca (Lexikon der Gesangsstimme. Geschichte. Wissenschaftliche Grundlagen. Gesangstechniken. Interpreten)

Gar keine Stimme? Wilhelmine Schröder-Devrient, Wagner und das Singen - Grotjahn, Rebecca (Bühnenrollen und Identitätskonzepte – Karrierestrategien von Künstlerinnen im Theater des 19. Jahrhunderts)

Der Wundersmann: Johann Sebastian Bach und die Kantate Wer nur den lieben Gott lässt walten BWV 93 - Grotjahn, Rebecca ("Ei, dem alten Herrn zoll’ ich Achtung gern'." Festschrift für Joachim Veit zum 60. Geburtstag)

Highly functionalized alkenes produced from base-free organocatalytic Wittig reactions: (E)-3-benzylidenepyrrolidine-2,5-dione, (E)-3-benzylidene-1-methylpyrrolidine-2,5-dione and (E)-3-benzylidene-1-tert-butylpyrrolidine-2,5-dione - Schirmer, Marie-Luis; Spannenberg, Anke; Werner, Thomas (Acta Crystallographica Section C Structural Chemistry)
The Wittig reaction is a fundamental transformation for the preparation of alkenes from carbonyl compounds and phosphonium ylides. The ylides are prepared prior to the olefination step from the respective phosphonium salts by deprotonation utilizing strong bases. A first free-base catalytic Wittig reaction for the preparation of highly functionalized alkenes was based on tributylphosphane as the catalyst. Subsequently we developed a system employing a phospholene oxide as a pre-catalyst and trimethoxysilane as reducing agent which operates under milder conditions. The title compounds, ( E )-3-benzylidenepyrrolidine-2,5-dione, C 11 H 9 NO 2 , (I), the methylpyrrolidine derivative, C 12 H 11 NO 2 , (II), and the tert- butylpyrrolidine derivative, C 15 H 17 NO 2 , (III), have been synthesized by base-free catalytic Wittig reactions. In the crystal of (I), molecules are linked into centrosymmetric dimers via pairs of N—H...O hydrogen bonds. Furthermore, in the crystal structure of (III), there are two molecules in the asymmetric unit, whereas in (I) and (II), only one molecule is present.
Keywords: Materials Chemistry; Inorganic Chemistry; Physical and Theoretical Chemistry; Condensed Matter Physics

A novel zinc based binary catalytic system for CO2utilization under mild conditions - Desens, Willi; Kohrt, Christina; Spannenberg, Anke; Werner, Thomas (Organic Chemistry Frontiers)
A novel zinc based binary catalytic system for the synthesis of cyclic carbonates under mild and solvent-free conditions utilizing CO2as a C1 building block is reported.
Keywords: Organic Chemistry

Novel Base-Free Catalytic Wittig Reaction for the Synthesis of Highly Functionalized Alkenes - Schirmer, Marie-Luis; Adomeit, Sven; Spannenberg, Anke; Werner, Thomas (Chemistry - A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Regio- and Stereoselective Synthesis of Dithiocarbonates under Ambient and Solvent-Free Conditions - Diebler, Johannes; Spannenberg, Anke; Werner, Thomas (ChemCatChem)
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Catalysis

Convergent Activation Concept for CO2Fixation in Carbonates - Desens, Willi; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

Atom economical synthesis of di- and trithiocarbonates by the lithium tert-butoxide catalyzed addition of carbon disulfide to epoxides and thiiranes - Diebler, J.; Spannenberg, A.; Werner, Thomas (Organic and Biomolecular Chemistry)
The lithium tert-butoxide catalyzed addition of CS2 to epoxides and thiiranes under mild conditions is reported. A mechanism has been proposed taking into account the regio- and stereochemical outcome of the reaction.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Biochemistry

Cooperative catalyst system for the synthesis of oleochemical cyclic carbonates from CO2and renewables - Tenhumberg, Nils; Büttner, Hendrik; Schäffner, Benjamin; Kruse, Daniela; Blumenstein, Michael; Werner, Thomas (Green Chemistry)
Taking Control!The binary catalyst system composed of MoO3and an organic phoshponium salt [Bu4P]X proved very efficient to produce oleochemical cyclic carbonates from renewables.
Keywords: Pollution; Environmental Chemistry

Alkoxide-Initiated Regioselective Coupling of Carbon Disulfide and Terminal Epoxides for the Synthesis of Strongly Alternating Copolymers - Diebler, Johannes; Komber, Hartmut; Häußler, Liane; Lederer, Albena; Werner, Thomas (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Iron-Based Binary Catalytic System for the Valorization of CO2 into Biobased Cyclic Carbonates - Büttner, Hendrik; Grimmer, Christoph; Steinbauer, Johannes; Werner, Thomas (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Organocatalyzed Synthesis of Oleochemical Carbonates from CO2and Renewables - Büttner, Hendrik; Steinbauer, Johannes; Wulf, Christoph; Dindaroglu, Mehmet; Schmalz, Hans-Günther; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Aufklärung und Imagination in Frankreich (1675-1810) - Anthologie und Analyse.

Cover Picture: Concise Synthesis of Dithiophene Derivatives by a Palladium- Catalyzed Multiple C-S Cross Coupling/Cyclization Sequence (Adv. Synth. Catal. 23/2016) - Oechsle, Peter; Hou, Peng; Flörke, Ulrich; Paradies, Jan (Advanced Synthesis & Catalysis)
Keywords: General Chemistry

Cycloisomerisierung von 1,5-Eninen über eine 5-endo-dig- Cyclisierungs-Protodeborylierungs-Sequenz mit einem frustrierten Lewis-Paar als Katalysator - Tamke, Sergej; Qu, Zheng-Wang; Sitte, Nikolai A.; Flörke, Ulrich; Grimme, Stefan; Paradies, Jan (Angewandte Chemie)

Cover Picture: Concise Synthesis of Dithiophene Derivatives by a Palladium- Catalyzed Multiple C-S Cross Coupling/Cyclization Sequence (Adv. Synth. Catal. 23/2016) - Oechsle, Peter; Hou, Peng; Flörke, Ulrich; Paradies, Jan (Advanced Synthesis & Catalysis)

Frustrated Lewis Pair Catalyzed Dehydrogenative Oxidation of Indolines and Other Heterocycles - Maier, Alexander F. G.; Tussing, Sebastian; Schneider, Tobias; Flörke, Ulrich; Qu, Zheng-Wang; Grimme, Stefan; Paradies, Jan (Angewandte Chemie International Edition)

Dehydrierende Oxidation von Indolinen und anderen Heterocyclen durch frustrierte Lewis-Paare - Maier, Alexander F. G.; Tussing, Sebastian; Schneider, Tobias; Flörke, Ulrich; Qu, Zheng-Wang; Grimme, Stefan; Paradies, Jan (Angewandte Chemie)

Frustrated Lewis Pair-Catalyzed Cycloisomerization of 1,5-Enynes via a 5-endo-dig Cyclization/Protodeborylation Sequence - Tamke, Sergej; Qu, Zheng-Wang; Sitte, Nikolai A.; Flörke, Ulrich; Grimme, Stefan; Paradies, Jan (Angewandte Chemie International Edition)

Frustrated Lewis Pair Catalyzed Dehydrogenative Oxidation of Indolines and Other Heterocycles - Maier, Alexander F. G.; Tussing, Sebastian; Schneider, Tobias; Flörke, Ulrich; Qu, Zheng-Wang; Grimme, Stefan; Paradies, Jan (Angewandte Chemie International Edition)

Concise Synthesis of Dithiophene Derivatives by a Palladium- Catalyzed Multiple C-S Cross Coupling/Cyclization Sequence - Oechsle, Peter; Hou, Peng; Flörke, Ulrich; Paradies, Jan (Advanced Synthesis & Catalysis)

Structure-Reactivity Relationship in the Frustrated Lewis Pair (FLP)-Catalyzed Hydrogenation of Imines - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry - A European Journal)

Heteroacene Synthesis through C−S Cross-Coupling/5-endo-digCyclization - Oechsle, Peter; Flörke, Ulrich; Egold, Hans; Paradies, Jan (Chemistry - A European Journal)

Inside Cover: Structure–Reactivity Relationship in the Frustrated Lewis Pair (FLP)‐Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Inside Cover: Structure-Reactivity Relationship in the Frustrated Lewis Pair (FLP)-Catalyzed Hydrogenation of Imines (Chem. Eur. J. 22/2016) - Tussing, Sebastian; Kaupmees, Karl; Paradies, Jan (Chemistry - A European Journal)

The concept of generalized stresses for computational manufacturing and beyond - Mahnken, Rolf; Cheng, Chun; Düsing, Martin; Ehlenbröker, Ulrich; Leismann, Thorben (GAMM-Mitteilungen)

PC expansion for material parameters using artificial data and statistical methods - Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

A linear elastic Fuzzy Finite Element Method with two fuzzy input parameters - Dridger, Alex; Caylak, Ismail; Mahnken, Rolf (PAMM)

SFEM for rubber-like materials at large deformations - Penner, Eduard; Caylak, Ismail; Nörenberg, Nicole; Mahnken, Rolf (PAMM)

Lehrbuch der Technischen Mechanik - Band 1: Starrkörperstatik - Mahnken, Rolf

Temperature-insensitive electro-optic response of polymer-stabilized blue phases - Nordendorf, Gaby; Schmidtke, Jürgen; Wilkes, David; Kitzerow, Heinz-Siegfried (Journal of Materials Chemistry C)
Polymer-stabilized blue phase liquid crystal in-plane switching cell.
Keywords: Materials Chemistry; General Chemistry

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers - Wahle, M.; Ebel, J.; Wilkes, D.; Kitzerow, Heinz-Siegfried (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Metallic and semiconducting nanoparticles in LCs - Sharma, Anshul; Urbanski, Martin; Mori, Taizo; Kitzerow, Heinz-Siegfried; Hegmann, Torsten (Series in Soft Condensed Matter)

Influence of Proton and Salt Concentration on the Chromonic Liquid Crystal Phase Diagram of Disodium Cromoglycate Solutions: Prospects and Limitations of a Host for DNA Nanostructures - Zhang, Bingru; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Physical and Theoretical Chemistry

Alignment and Graphene-Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva-Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz-Siegfried (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Integral representation and sharp asymptotic results for some Heckman-Opdam hypergeometric functions of type BC - Rösler, Margit; Voit, Michael (Transactions of the American Mathematical Society)

A multivariate version of the disk convolution - Rösler, Margit; Voit, Michael (Journal of Mathematical Analysis and Applications)
Keywords: Applied Mathematics; Analysis

Time-Resolved Mueller Matrix Measurement and Polarization Scrambler Characterization - Koch, Benjamin; Noé, Reinhold; Mirvoda, Vitali (2016 21ST EUROPEAN CONFERENCE ON NETWORKS AND OPTICAL COMMUNICATIONS (NOC))

Erklärungsfaktoren für Einstellungen von Schülerinnen und Schülern im Grundschulalter gegenüber Kindern mit sonderpädagogischem Förderbedarf – Ergebnisse aus einer empirischen Studie. Vortrag auf der 51. Arbeitstagung der Dozierenden der Sonderpädagogik in deutschsprachigen Ländern „Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik“ - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

Leistungsrückmeldungen im Zusammenhang mit Leseleistungen, Selbstwirksamkeitsüberzeugungen und Kausalattributionen bei Kindern im dritten und vierten Grundschuljahr. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Ort, Margarita; Hellmich, Frank

Prädiktoren für Einstellungen und Motivation bei Studentinnen und Studenten des Lehramts an Grundschulen in Bezug auf den inklusiven Unterricht. Vortrag auf der 51. Arbeitstagung der Dozierenden der Sonderpädagogik in deutschsprachigen Ländern „Sonderpädagogik zwischen Wirksamkeitsforschung und Gesellschaftskritik“ - Görel, Gamze; Hellmich, Frank

Engineering the Frequency Spectrum of Bright Squeezed Vacuum via Group Velocity Dispersion in an SU(1,1) Interferometer - Lemieux, Samuel; Manceau, Mathieu; Sharapova, Polina; Tikhonova, Olga V.; Boyd, Robert W.; Leuchs, Gerd; Chekhova, Maria V. (Physical Review Letters)
Keywords: General Physics and Astronomy

Tunable optical parametric generator based on the pump spatial walk-off - Cavanna, Andrea; Just, Felix; Sharapova, Polina; Taheri, Michael; Leuchs, Gerd; Chekhova, Maria V. (Optics Letters)
Keywords: Atomic and Molecular Physics; and Optics

Förderung inklusiven Lernens im naturwissenschaftlich-technischen Sachunterricht der Grundschule. Vortrag auf der 4. Jahrestagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Blumberg, Eva; Fromme, Theresa; Hellmich, Frank

Zur Feinstaubabscheidung aus Holzfeuerungsanlagen mit precoatierten Oberflächenfiltern - Schiller, Sascha

Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents - Lopez Salas, Nieves; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F. (Journal of Materials Chemistry A)
DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Kinder mit Lernschwierigkeiten in der Grundschule - Miller, Susanne; Kottmann, Brigitte (Differenz - Ungleichheit - Erziehungswissenschaft)

"Und dann war das auch noch so ein kleines, zartes Persönchen": Grundschullehrkräfte im Entscheidungsdilemma zwischen Fördern und Selektieren - Miller, Susanne; Kottmann, Brigitte (Diagnostik im Kontext inklusive Bildung)

Selektion inklusive?! Widersprüche bei der umsetzung von Inklusion in der Schule - Kottmann, Brigitte; Miller, Susanne (Empirische Forschung im Kontext Schule)

Quantum technology: from research to application - Schleich, Wolfgang P.; Ranade, Kedar S.; Anton, Christian; Arndt, Markus; Aspelmeyer, Markus; Bayer, Manfred; Berg, Gunnar; Calarco, Tommaso; Fuchs, Harald; Giacobino, Elisabeth; Grassl, Markus; Hänggi, Peter; et al. (Applied Physics B)
Keywords: General Physics and Astronomy; Physics and Astronomy (miscellaneous); General Engineering

In-lab ALOHA mid-infrared up-conversion interferometer with high fringe contrast @λ = 3.39 μm - Szemendera, L.; Darré, P.; Baudoin, R.; Grossard, L.; Delage, L.; Herrmann, Harald; Silberhorn, Christine; Reynaud, F. (Monthly Notices of the Royal Astronomical Society)
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Local Sampling of the Wigner Function at Telecom Wavelength with Loss-Tolerant Detection of Photon Statistics - Harder, G.; Silberhorn, Christine; Rehacek, J.; Hradil, Z.; Motka, L.; Stoklasa, B.; Sánchez-Soto, L. L. (Physical Review Letters)
Keywords: General Physics and Astronomy